Motivation to Writing Articles for Islamic Religious Education Teachers at MTsN 10 Pesisir Selatan - Noprijon; Martin Kustati; Rezki Amelia (Universitas Muhammadiyah Palu, 2025)
This study aims to determine and analyze the motivation of Islamic Religious Education (PAI) teachers in writing scientific articles at MTsN 10 Pesisir Selatan. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation. The results of the study indicate that the motivation of PAI teachers in writing articles is influenced by intrinsic factors, such as encouragement of professional development, the desire to share knowledge, and self-actualization; as well as extrinsic factors, such as demands for career development, awards from institutions, and encouragement from colleagues. However, challenges such as time constraints, lack of writing training, and lack of access to scientific journals are still obstacles. This study recommends the need for ongoing scientific writing training, stronger institutional support, and strengthening of academic culture in the madrasah environment.